Sexual fantasies, subjective satisfaction and quality of sexual life in patients of sexual dysfunction: A comparative study. (13th April 2021) - Ohri, N.; Dubey, A.; Vankar, G.; Rathi, P.; Gill, A.
Abstract : Introduction: Exploring the ways in which sexual fantasies may affect sexual experience and satisfaction is of relavence in the clinical setting involving sexual dysfuntion. Objectives: To observe how the sexual fantasy scores differ in their relationship with sexual satisfaction, experience and quality between sexual dysfunction cases and normal controls. Methods: Scales included: Wilson's sex fantasy questionnaire (WSFQ), Arizona Sexual Experience Scale (ASEX), Sexual Quality of life Questionnaire (SQoL), and a subjective sexual satisfaction meter. Differences in resposes of both groups on WSFQ (item-wise and domain-wise) were analysed using T-tests. Two-way ANOVA was applied to see how other scales affected sexual fantasy. Results: Cases scored significantly higher on ASEX scale, and low on satisfaction, SQoL and WSFQ Cases N=1OO Controls N=100 t-test Satisfaction Mean(sd) 4.27(1.85) 7.82(1.31) t=3.052;df=198, p=0.0026 Asex 17.52(4.73) 8.28(1.34) t=15.24;df=198, p<0.0001 SQoL 29.41(12.12) 49.5(6.67) t=14.52;df=198, p<0.0001 WSFQ 26.80(17.61) 30.59(15.32) t=1.62, df=98, p=0.106 Majority of WSFQ responses, both in cases and controls, fell in the intimate and impersonal domains. Sexual fantasy scores and sexual satisfaction had a strong positive and significant correlation in controls but no linear correlation in the case-subjects. sexual fantasy scores contributed to 5.7% of difference in the scores of SQoL between groups. Major variance in scores of satisfaction in our subjects depended on presence or absence of sexual dysfunction(46.5%)but sexual fantasies also contributed to 8.8% of the variance. Conclusions: The study showed that fantasies contribute to positive sexual outcomes only in absence of sexual dysfunction. ANOVAanalysis revealed that in case-subjects sexual satisfaction briefly increases initially with increase in fantasy scores but starts to decline as fantasies increase. Disclosure: No significant relationships.